Cultivation of Edible Tropical Bolete, Phlebopus spongiosus, in Thailand and Yield Improvement by High-Voltage Pulsed Stimulation - Jaturong Kumla; Nakarin Suwannarach; Saisamorn Lumyong (Agronomy, 2022)
Tropical bolete, Phlebopus spongiosus, is an edible ectomycorrhizal mushroom indigenous to northern Thailand. This mushroom has the ability to produce fruiting bodies without the need for a host plant. In this study, the technological cultivation of P. spongiosus was developed. Cultivation experiments indicated that fungal mycelia could completely colonize the cultivation substrate over a period of 85–90 days following inoculation of liquid inoculum. Primordia were induced under lower temperatures, high humidity and a 12-h photoperiod. Mature fruiting bodies were developed from young fruiting bodies within a period of one week. Consequently, yield improvement of P. spongiosus cultivation was determined by high-voltage pulsed stimulation. The results indicated that the highest degree of primordial formation, number of mature fruiting bodies and total weight values were obtained in cultivation experiments involving a high voltage of 40 kV. The total weight of the mushrooms increased by 1.4 times after applying high-voltage pulses when compared with the control. Additionally, the results revealed that the size of the fruiting body and the proximate composition of the fruiting bodies from high-voltage stimulation treatments were not different from the control. This research provides valuable information concerning successful cultivation techniques and yield improvement by high-voltage pulsed stimulation for the large-scale commercial fruiting body production of P. spongiosus.